The Edmonton Encampment Litigation and The Charter Claims We Didn’t (Get to) Argue - Lund, Anna (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2024)
In recent years, the number of unhoused and unsheltered individuals in Canada has risen dramatically. In urban centres across Canada, unsheltered individuals have gathered together in encampments for safety and a sense of community. Municipalities frequently respond to these encampments by forcibly evicting them. In autumn 2023, the Coalition for Justice and Human Rights filed a claim on behalf of Edmonton’s encampment residents, alleging their rights and freedoms, as enshrined in the Canadian Charter of Rights and Freedoms sections 2, 7, 8, 12, and 15, were unjustifiably infringed by the City of Edmonton'’s encampment displacement policies and practices. The case was struck on a preliminary ground, because the court held that the Coalition lacked public interest standing, and thus the court never made a decision on the merits of the Coalition's Charter claims. This article provides a procedural chronology of the Edmonton encampment case and sets out the Charter arguments that the Coalition planned to advance. In doing so, this article aims to offer guidance to others engaged in encampment litigation, to broaden the conversation about how the Charter is implicated in encampments and governmental responses to them, and to give voice to the unhoused individuals, who provided evidence in support of the Coalition's lawsuit.